Ayurveda's Impact on Anemia among Rural School Children in Belagavi, Karnataka: An Observational Study - Sagare, Sandeep Subhash; Buduru, Srinivas Prasad; Sutagatti, Kavita; Mulla, Zeba (International Journal of Pharmaceutical Investigation, 2025)
Background/Purpose Anemia poses a significant public health challenge, particularly in developing nations. Indian government has initiated several programs aimed at reducing the prevalence of anemia, such as providing iron and folic acid supplements and Mid-day meals to school-aged children. This study aims to address the issue by employing Ayurveda's comprehensive approach and cooperation. Materials and Methods A survey of baseline was conducted on 7101 children from 41 schools and 85 Anganwadis by Hudali Primary Health Centre. A period of one academic year, 2022-23 out of 7101 Children's 301 instances were evaluated for anaemia. The data was analyzed using appropriate software and statistical methods. Results The height, weight, and Body mass index measurements during the first to third follow-up revealed that there was a statistically significant mean difference for the weight and BMI variables when comparing the initial screening to the follow-up assessments. Hb% observed differences are statistically significant between screening and follow-up measurements. The initial serum ferritin level before treatment was 75.7579 (SD: 57.04) for a sample size of 293. After treatment, the serum ferritin level rose to 128.3211 (SD: 70.25) within the same sample size. Conclusion Childhood anemia remains a significant public health issue within this age group. Our research highlights the substantial prevalence of anemia among school-age children. The effectiveness of intervention drugs in treating anemia was noted. We recommend the need for thorough, well-organized, and extensive investigations that use standardized methods to assess the occurrence and treat anemia.
Keywords: Anemia; Ayurveda; Rural School; Illness; BMI